Cl(−) Secretion in Colonic Epithelial Cells Induced by the Vibrio parahaemolyticus Hemolytic Toxin Related to Thermostable Direct Hemolysin - Takahashi, Akira (American Society for Microbiology, 2000)
A hemolytic toxin related to thermostable direct hemolysin (TDH), TDH-related hemolysin (TRH), produced by Kanagawa-phenomenon-negative Vibrio parahaemolyticus is suspected of playing an important, but yet-to-be-elucidated role in diarrhea caused by this organism. In cultured human colonic epithelial cells, TRH increases Cl(−) secretion, followed by elevation of intracellular calcium.